THE EFFECT OF DIGITAL SKILLS AND MARKET FEASIBILITY ON STARTUP PERFORMANCE: THE MODERATING ROLE OF TVET TRAINING - Kiki Ameliza (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study examines the effect of digital skills and market feasibility on startup performance, with Technical and Vocational Education and Training (TVET) acting as a moderating variable. The rapid digital transformation has reshaped entrepreneurial ecosystems, making digital competence and market alignment essential for startup survival. Using a quantitative explanatory design, data were collected from 100 startup founders through structured questionnaires. The results show that digital skills have a significant positive effect on startup performance, demonstrating how technological proficiency enhances innovation, operational efficiency, and competitiveness. In contrast, market feasibility reveals a significant but negative effect, suggesting possible misinterpretation of market conditions or oversaturation within competitive industries. TVET training emerges as the strongest predictor, indicating its crucial role in equipping entrepreneurs with practical competencies, hands-on problem-solving skills, and technical readiness. Furthermore, TVET training moderates the effects of digital skills and market feasibility, strengthening the relationship between these predictors and performance outcomes. The findings emphasize the importance of integrating digital literacy and vocational training within entrepreneurial development programs. This study contributes to theoretical understanding and provides practical insights for policymakers, educators, and startup ecosystem stakeholders. Keywords: Digital Skills, Market Feasibility, Startup Performance, TVET Training, Entrepreneurship Abstrak: Penelitian ini menganalisis pengaruh keterampilan digital dan kelayakan pasar terhadap kinerja startup, dengan pelatihan Pendidikan dan Pelatihan Teknik dan Vokasional (TVET) sebagai variabel moderasi. Transformasi digital yang cepat telah mengubah ekosistem kewirausahaan, sehingga kompetensi digital dan kesesuaian pasar menjadi faktor penting bagi keberhasilan startup. Penelitian ini menggunakan pendekatan kuantitatif eksplanatori dengan mengumpulkan data dari 100 pendiri startup melalui kuesioner terstruktur. Hasil penelitian menunjukkan bahwa keterampilan digital berpengaruh positif signifikan terhadap kinerja startup, menegaskan bahwa kemampuan teknologi meningkatkan inovasi, efisiensi operasional, dan daya saing. Sebaliknya, kelayakan pasar menunjukkan pengaruh signifikan namun negatif, yang dapat mencerminkan kesalahan interpretasi kondisi pasar atau persaingan industri yang jenuh. Pelatihan TVET menjadi prediktor paling kuat, menegaskan perannya dalam membekali wirausaha dengan kompetensi praktis, kemampuan pemecahan masalah, dan kesiapan teknis. Selain itu, TVET memoderasi pengaruh keterampilan digital dan kelayakan pasar, memperkuat hubungan antara variabel prediktor dan kinerja. Temuan ini menekankan pentingnya integrasi literasi digital dan pelatihan vokasional dalam program pengembangan kewirausahaan. Penelitian ini memberikan kontribusi teoretis dan wawasan praktis bagi pembuat kebijakan, pendidik, dan pemangku kepentingan ekosistem startup. Kata Kunci: Keterampilan Digital, Kelayakan Pasar, Kinerja Startup, Pelatihan TVET, Kewirausahaan